Ślady Orygenesowej egzegezy w „De monastica exercitatione” Nila z Ancyry - Nieścior, Leon (Vox Patrum, 2019)
In his main work on monastic asceticism, De monastica exercitatione, Nilus of Ancyra (died around 430) uses many allegorical explanations of the Bible, especially of the Old Testament. Some of them seem to have traces of Origen's influence. We find the Alexandrian’s influence, direct or indirect, in the Nilus of Ancyra’s allusions to: Gen. 3: 15, Judg. 15: 4, 1 Sam. 14: 13, Ps. 137: 9, Lam. 4: 5, Zech. 11: 17. If Origen in these cases uses allegorics on doctrinal and ascetical grounds, the Nilus of Ancyra narrows it down to the ascetic subject.